Preparation method and application of coating, testing method and sulfur deposition amount measuring device
By combining modified hydrophilic nanoparticles and specific resins, a coating with sulfur-removing properties is prepared and applied to the inner wall of the wellbore of a high-sulfur gas field, the sulfur deposition problem is solved, and the effect of reducing the amount of sulfur deposition and improving the stability of the coating is achieved.
Patent Information
- Application Number
- CN202411862328.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-02-28
AI Technical Summary
The problem of sulfur deposition in wellbores in high sulfur gas fields has led to a decrease in gas well production and pipeline blockage. The existing technology is mainly for post-relieving cleaning, and there is a lack of effective methods to prevent sulfur deposition from the source.
A coating preparation method is adopted to prepare a coating with sulfur-removing properties by combining modified hydrophilic nano SiO2, ZnO or Al2O3 with specific solvents and resins, and it is applied to the inner wall of the wellbore or the collection and transportation pipeline system to reduce sulfur deposition.
It effectively reduces the amount of sulfur deposition, improves the mechanical stability and corrosion resistance of the coating, solves the sulfur deposition problem from the source, and improves gas well production and pipeline smoothness.
Smart Images

Figure CN119529671A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coating materials, and in particular to a coating preparation method and application, a testing method and a sulfur deposition amount measuring device. Background Art
[0002] The phenomenon of sulfur deposition in the wellbore of a high-sulfur gas field refers to the process in which, as the pressure and temperature decrease from the formation to the ground gathering and transportation system, the sulfur in the natural gas will precipitate and form sulfur crystals. When these sulfur particles are too large to be carried away by the airflow, sulfur deposition will occur. At the same time, during the mining process, the consumption of heavy components will also accelerate the sulfur precipitation process. If the temperature of the precipitation point is higher than the solidification point of elemental sulfur at the pressure at that point, the precipitated sulfur will be in a liquid state; otherwise, the sulfur will be in a solid state. When the airflow cannot carry the sulfur particles, the sulfur particles will deposit and cause blockage and corrosion problems in the gas field pipeline. Sulfur deposition problem in the wellbore of a high-sulfur gas field The sulfur deposition problem mainly occurs in key parts such as separators, throttle valves, and manifolds in the gas field mining wellbore or gathering and transportation pipeline system. For example, a high-sulfur gas field in the Sichuan Basin faces serious sulfur deposition challenges. Sulfur deposition blockage is mainly manifested in the blockage of ground equipment and wellbore. Among them, sulfur blocks 70% of gas wells, causing a sharp drop in gas well production, which has a serious impact on natural gas development. Figure 1 Schematic diagram of sulfur deposition blocking a pipeline.
[0003] Existing solutions to the problem of sulfur deposition in high-sulfur gas field wellbores include regular mechanical cleaning, heating to remove blockages, and optimizing natural gas production processes. The regular mechanical cleaning method requires interrupting the production schedule; the heating to remove blockages can usually only melt the surface sulfur and cannot solve the problem of serious pipeline blockages; improving the natural gas production process can usually only slow down the deposition rate of deposited sulfur. It can be seen that the existing technology usually relieves sulfur deposition after it is formed, and rarely considers solutions to prevent sulfur deposition from forming at the source. Summary of the invention
[0004] The main purpose of the present invention is to propose a method for preparing and applying a coating, so as to provide a new idea for solving the problem of sulfur deposition in the production of high-sulfur gas fields; the second purpose of the present invention is to propose a test method for the sulfur contact angle and the sulfur rolling angle on the coating surface, and to propose a device for measuring the sulfur deposition amount, which are applied to the coating prepared by the aforementioned preparation method. Through the above specific test method and the sulfur deposition amount measuring device, the improvement degree of the sulfur deposition problem of the formed coating in the wellbore of a high-sulfur gas field can be comprehensively evaluated, and a specific and feasible performance evaluation scheme is provided.
[0005] To achieve the above object, the present invention provides a method for preparing a coating, comprising the following preparation steps:
[0006] S A1: Dispersing hydrophilic nano-SiO2 in a solvent, then adding ethyl orthosilicate, ammonia water and 1H,1H,2H,2H-heptadecafluorodecyltrimethoxysilane into the solvent for reaction, and modifying to obtain a first product; or, S A1 : Adding hydrophilic nano ZnO and 1H,1H,2H,2H-heptadecafluorodecyltrimethoxysilane into a solvent for reaction, and modifying to obtain a first product;
[0007] S A2 :S A1 The first product is dispersed in a butyl acetate solution to obtain a sol solution, and a fluorosilicone resin and a curing agent are added to the sol solution to carry out a cross-linking reaction to prepare a coating;
[0008] The weight ratio of the first product, the butyl acetate solution, the fluorosilicone resin and the curing agent is 100wt% in total, the first product is 8-16wt%, and the weight ratio of the butyl acetate: the fluorosilicone resin: the curing agent is 5-15: 1-3: 0.1-0.3.
[0009] Or use the following steps:
[0010] S B1 : Add hydrophilic nano-Al2O3 and 1H,1H,2H,2H-heptadecafluorodecyltrimethoxysilane into a solvent for reaction, and modify to obtain a first product;
[0011] S B2 :S B1 The first product is dispersed in an ethyl acetate solution to obtain a sol solution, and then an epoxy resin and a curing agent are added to the sol solution to carry out a cross-linking reaction to prepare a coating;
[0012] The weight ratio of the first product, the ethyl acetate solution, the epoxy resin and the curing agent is 100wt% in total, the first product is 16-24wt%, and the weight ratio of the ethyl acetate: the epoxy resin: the curing agent is 5-15:1-3:1-3.
[0013] The present invention first modifies hydrophilic nanoparticles (hydrophilic nano-SiO2, hydrophilic nano-ZnO and hydrophilic nano-Al2O3) with 1H,1H,2H,2H-heptadecafluorodecyltrimethoxysilane to form a first product with low surface energy. The above method is usually used to prepare a precursor of a super-hydrophobic coating, and low-surface-energy substances are usually difficult to adhere to the surface of a substrate. In the subsequent step, the present invention modifies the hydrophilic nanoparticles (hydrophilic nano-SiO2, hydrophilic nano-ZnO and hydrophilic nano-Al2O3) with a specific mass percentage of the first product (the first product prepared by hydrophilic nano-SiO2 and hydrophilic nano-ZnO) into a first product with a specific mass ratio. A coating having qualified coating quality and sulfur-repellent and low-sulfur properties is prepared by mixing a first product (a first product prepared by hydrophilic nano-Al2O3) with a butyl acid solution, a fluorosilicone resin and a curing agent, or mixing a first product (a first product prepared by hydrophilic nano-Al2O3) with a specific mass percentage into an ethyl acetate solution, an epoxy resin and a curing agent having a specific mass ratio combination, to prepare a coating having qualified coating quality and sulfur-repellent and low-sulfur properties. Sulfur-repellent and low-sulfur properties refer to the coating formed by curing the coating having sulfur-repellent properties and the performance of reducing the amount of solid sulfur deposition. The sulfur-repellent property refers to a sulfur contact angle greater than 90°. The qualified coating quality refers to the coating having no obvious cracking and an adhesion performance of more than level 2 (including level 2).
[0014] When hydrophilic nano-SiO2 is used as the raw material, the modified silica is prepared by the sol-gel method. SiO2 generated by the hydrolysis of ethyl orthosilicate under the catalysis of ammonia water forms a composite structure with the added hydrophilic nano-SiO2, and then grafted with 1H, 1H, 2H, 2H-heptadecafluorodecyltrimethoxysilane, and mixed in the coating to more easily obtain a micro-nano structure. And because SiO2 is generated under alkaline catalyst conditions, it has more -OH groups on the surface, so it is easier to be grafted, so that the powder has better sulfur-repellent properties.
[0015] Specifically, in step S A1 or step S B1 In the above method, the solvent is any one of ethanol, toluene and acetone. The above solution is conducive to the dispersion of hydrophilic nanoparticles and the subsequent low surface energy modification reaction.
[0016] Preferably, in step S A2 In step S, the first product is 10 to 14 wt%; or B2 The first product is 18-22 wt %. The coating prepared by the first product of the preferred mass percentage has better sulfur-repelling and low-sulfur properties and coating quality after curing.
[0017] Further preferably, in step S A2 In step S, the first product is 14 wt%; the weight ratio of butyl acetate: fluorosilicone resin: curing agent is 10:3:0.3; or, in step S B2wherein the first product is 20 wt%; the weight ratio of the ethyl acetate: the epoxy resin: the curing agent is 10:2:2. The coating after curing has the best sulfur-repellent and low-sulfur performance, coating quality and sulfur-repellent stability. The curing agent is preferably Bayer's 3390 curing agent.
[0018] Preferably, the particle size of the nano-SiO2 is 7 to 40 nm. Nano-SiO2 within the preferred particle size range is beneficial for constructing a micro-nano structure in the coating.
[0019] Preferably, S A1 The reaction temperature is 10℃~50℃; S A2 The reaction temperature is 0℃~
[0020] 70°C. The corresponding steps can be well modified or cross-linked at this temperature.
[0021] The present invention provides an application of the coating in the above scheme, wherein the coating prepared by the coating preparation method described in any of the above schemes is applied to the inner wall of a wellbore for exploitation of a high-sulfur gas field or the inner wall of a pipeline of a gathering and transportation pipeline system. The coating maintains stable sulfur-repelling performance and performance of reducing sulfur deposition within the sulfur deposition temperature range, and the coating also has good mechanical stability and corrosion resistance, so that solid sulfur deposition in the wellbore or gathering and transportation pipeline system can be reduced from the source.
[0022] The present invention also provides a method for testing the sulfur contact angle of a coating surface, which is applied to a coating prepared by any of the aforementioned preparation methods; the method comprises the following steps:
[0023] S D1 , applying the aforementioned coating to the surface of the substrate and curing to obtain a test sample of the surface-adherent coating;
[0024] S D2 , respectively heating the test sample and solid sulfur to 120-160° C., and waiting for the solid sulfur to liquefy;
[0025] S D3 , Conduct sulfur contact angle test:
[0026] The test sample is placed on a contact angle test platform, liquid sulfur is drawn and dropped onto the surface of the test sample, and a static contact angle image of the liquid sulfur is taken before the liquid sulfur is cooled and solidified to measure the sulfur contact angle.
[0027] In a specific embodiment, in order to obtain the sulfur contact angle before the liquid sulfur is cooled and solidified, the tester needs to photograph the sulfur contact angle as quickly as possible. In a preferred embodiment, the temperature of the liquid sulfur is maintained at ≥120°C during the test. The liquid sulfur is kept at a temperature above 120°C to avoid solidification of the liquid sulfur. In order to save energy and reduce consumption, the temperature of the liquid sulfur is preferably maintained at 120°C to 130°C, and most preferably, the temperature of the liquid sulfur is maintained at 120°C.
[0028] Specifically, the temperature of the liquid sulfur is maintained by installing a heating platform on the surface of the contact angle test platform, and the test sample is placed on the heating platform.
[0029] Preferably, the substrate is a nickel-based alloy, a zinc sheet, or an iron sheet. In a gathering and transportation system, such as a gathering and transportation pipeline system for gas field exploitation, the pipeline material is usually a nickel-based alloy.
[0030] The present invention also provides a method for testing the sulfur rolling angle on the coating surface, which is applied to the coating prepared by any of the above-mentioned preparation methods; and comprises the following steps:
[0031] S E1 , applying the aforementioned coating to the surface of the substrate and curing to obtain a test sample of the surface-adherent coating;
[0032] S E2 , respectively heating the test sample and solid sulfur to 120-160° C., and waiting for the solid sulfur to liquefy;
[0033] S E3 , Conduct sulfur rolling angle test:
[0034] The test sample is placed on a contact angle test platform, and liquid sulfur is dropped onto the surface of the test sample. The temperature of the liquid sulfur is maintained at ≥120°C, and the horizontal angle of the contact angle test platform is gradually increased. Photos of the droplets just rolling down are taken to obtain micro-rolling angle data, and the sulfur rolling angle is measured.
[0035] During the sulfur rolling angle test, the horizontal angle of the contact angle test platform needs to be gradually increased. If the temperature is not maintained, the liquid sulfur will have cooled and solidified into solid sulfur during this period. Therefore, the liquid sulfur must be kept at a temperature above 120°C to avoid solidification of the liquid sulfur when testing the sulfur rolling angle. In order to save energy and reduce consumption, it is preferred to maintain the temperature of the liquid sulfur at 120°C to 130°C, and most preferably, the temperature of the liquid sulfur is maintained at 120°C. Specifically, the liquid sulfur temperature is maintained by installing a heating platform on the surface of the contact angle test platform, and the test sample is placed on the heating platform.
[0036] The present invention also provides a sulfur deposition amount measuring device, which is applied to a coating prepared by any of the above-mentioned preparation methods, wherein the coating is applied to a substrate surface and cured to obtain a test sample of a surface-attached coating; the device comprises: a gas mixing system, a gas supply system, a test container system, a sulfur recovery container system and a three-way valve, wherein the gas mixing system, the gas supply system and the test container system are connected via the three-way valve, and the sulfur recovery container system is connected to the test container system, wherein:
[0037] The gas supply system supplies gas to the gas mixing system, the gas mixing system heats and sublimates solid sulfur and mixes gaseous sulfur with gas to form a mixed gas, which is then introduced into the test container system, the test container system places the test sample and allows the mixed gas to pass through the test sample at a predetermined flow rate and a predetermined pressure within a predetermined time, and the sulfur recovery container system cools and solidifies the mixed gas discharged from the test container system and collects solid sulfur;
[0038] The three-way valve comprises a first channel, a second channel and a third channel;
[0039] The gas mixing system comprises a gas container, the gas container is provided with a heating device, and the gas container is connected to the three-way valve through the first channel;
[0040] The gas supply system comprises a gas cylinder, the gas cylinder is connected to the second channel via a first pipeline, and the first pipeline is connected to a first pressure gauge;
[0041] The test container system comprises a test container, the test container is connected to the third channel through a second pipeline, the second pipeline comprises a flow valve and a second pressure gauge, and the test container outlet is connected to the sulfur recovery container system through the third pipeline;
[0042] The sulfur recovery container system comprises a sulfur recovery container, the sulfur recovery container is loaded with a cooling liquid, and the third pipeline outlet leads to the cooling liquid.
[0043] Specifically, the flow valve is used to adjust the gas flow entering the test container, and the flow valve is preferably a fine-tuning valve. The first pressure gauge is used to monitor the gas pressure entering the gas container, and the second pressure gauge is used to monitor the gas pressure entering the test container. The first pressure gauge and the second pressure gauge are preferably precision pressure gauges.
[0044] Preferably, a metal mesh is provided at the outlet of the test container, and the mesh opening of the metal mesh is less than 100 meshes. The metal mesh with the above mesh number is helpful to intercept the solid sulfur particles carried by the mixed gas in the test container when passing through.
[0045] Preferably, the sulfur recovery container is a beaker, the coolant is water, and the coolant may also be alcohol. Specifically, the heating device may be an oven or the like.
[0046] Preferably, the gas loaded in the gas cylinder may be carbon dioxide, nitrogen or natural gas, etc.
[0047] The present invention provides a method for using the above-mentioned sulfur deposition amount measuring device, comprising the following steps:
[0048] S C1 , placing solid sulfur in a gas container, turning on a heating device so that the temperature in the gas container is 120-160° C., and the solid sulfur melts and sublimates;
[0049] S C2 , open the first channel and the second channel of the three-way valve so that the gas supply system can supply gas to the gas mixing system, stop ventilation when the pressure is 1-3 MPa, close the second channel so that the gas container is in a closed state, and gaseous sulfur is mixed with the gas; at a temperature of 120-160°C, sulfur can maintain a gaseous state and mix quickly with the gas.
[0050] S C3 , open the third channel of the three-way valve, preheat for more than 10 minutes, then pass the mixed gas into the test container through the second pipe at a predetermined flow rate and a predetermined pressure, place the relevant test sample in the test container, record the ventilation time, and measure the sulfur deposition amount on the surface of the test sample at the predetermined time. If the mixed gas is directly introduced after the third channel is opened, the gaseous sulfur in the mixed gas will easily cool and solidify in the third channel of the three-way valve to form a deposit after contacting the three-way valve. By preheating for more than 10 minutes to increase the temperature of the three-way valve as a whole, the gaseous sulfur in the mixed gas will not easily solidify after contacting the three-way valve.
[0051] Specifically, by recording the initial weight of the relevant test sample and then recording the total weight of the relevant test sample after ventilation, the difference between the two values is the sulfur deposition amount.
[0052] Beneficial effects: The present invention prepares a coating with qualified coating quality and improved sulfur-repellent and low-sulfur performance by mixing an appropriate amount of the first product into a butyl acetate solution, a fluorosilicone resin and a curing agent having a specific mass ratio combination. The coating is applied to the inner wall of a wellbore or the inner wall of a pipeline system for the exploitation of a high-sulfur gas field, and can reduce the solid sulfur deposition in the wellbore or the pipeline system from the source, providing a new idea for solving the sulfur deposition problem in the wellbore of a high-sulfur gas field. The present invention also provides a test method for the sulfur contact angle and the sulfur rolling angle of the coating surface and a device for measuring the sulfur deposition amount, providing a specific performance evaluation scheme for the coating in terms of sulfur-repellent and low-sulfur improvement. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying any creative work.
[0054] Figure 1 A schematic diagram of heavy sulfur deposition in a pipeline in the background art;
[0055] Figure 2 A schematic diagram showing the improvement of sulfur deposition on a nickel-based alloy sheet by using the coating of the present invention;
[0056] Figure 3 This is an example of a sulfur contact angle image taken using the sulfur contact angle measurement method of the present invention;
[0057] Figure 4 This is an example of a sulfur rolling angle image taken using the sulfur rolling angle measurement method of the present invention;
[0058] Figure 5 This is a diagram of a device for measuring the amount of sulfur deposition using the present invention.
[0059] Description of the drawings: 1-gas mixing system, 11-heating device, 12-gas container, 2-gas supply system, 21-first pipeline, 22-first pressure gauge, 23-gas cylinder, 3-three-way valve, 31-first channel, 32-second channel, 33-third channel, 4-test container system, 41-second pipeline, 42-flow valve, 43-second pressure gauge, 44-test sample, 45-test container, 5-sulfur recovery container system, 51-third pipeline, 52-sulfur recovery container, 53-cooling liquid.
[0060] The realization of the purpose, functional features and advantages of this application will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0061] The technical solutions in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in this field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0062] The technical scheme of the present invention is further described in detail below in conjunction with specific embodiments or comparative examples. In the following embodiments and comparative examples, raw materials, reagents, etc. not otherwise specified are all commercially available, and the same batch of raw materials or reagents are used in the embodiments and comparative examples; the preparation methods without special conditions are all prepared by conventional, well-known preparation methods.
[0063] The curing agent is Bayer's 3390 curing agent, the substrate in the test sample is made of nickel-based alloy, and the nickel-based alloy used in the specific embodiment and the comparative example is specifically Hastelloy C276.
[0064] The test samples of the specific embodiments or specific comparative examples of the present invention are measured by the following methods or standards:
[0065] Test method description:
[0066] 1. Low sulfur performance
[0067] 1.1 Determination of sulfur deposition
[0068] Place the test sample of the specific embodiment or the specific comparative example on the adjacent Figure 5 The device simulates the precipitation and deposition of solid sulfur during natural gas extraction, and records the amount of sulfur deposited on the test sample after a period of time. The less sulfur deposited on the test sample in the same period of time, the better its sulfur-repelling performance.
[0069] 1.2 Test description of sulfur deposition
[0070] The experimental wellbore inner wall material Hastelloy C276 simulated the wellbore inner wall for sulfur deposition experiment. First, connect the experimental instrument, put 500g of solid sulfur into the gas container in the displacement oven, connect the left valve channel of the three-way valve to the 6mm pipe through the precision pressure gauge and fine-tuning valve to the test container, and place the test sample in the test container. The right valve channel connects the 3mm pipe to the carbon dioxide cylinder. A metal mesh with dense gaps is placed at the outlet of the test container to intercept the solid sulfur carried in the mixed gas, and the 3mm pipeline is connected to a beaker filled with water to intercept the solid sulfur formed by cooling.
[0071] 1.3 Sulfur deposition test method
[0072] First, open the displacement oven to melt and sublimate the solid sulfur, open the valve channels on both sides of the three-way valve, inject the carbon dioxide in the carbon dioxide cylinder into the gas container, observe the pressure, and when the pressure reaches the predetermined value (1-3MPa), stop ventilation and close the valves on both sides of the gas container to make it closed. After heating for 20 minutes, the solid sulfur is vaporized and mixed into the carbon dioxide gas. Finally, open the fine-tuning valve to allow the carbon dioxide containing gaseous sulfur to pass into the test container, and record the ventilation time. At this time, the sulfur-containing gas passes through the surface of the test sample and is deposited. Weigh the sulfur content on the surface of the test sample to draw experimental conclusions.
[0073] 2. Coating quality (adhesion and cracking evaluation)
[0074] Observe whether the coating on the test sample of the specific embodiment or the specific comparative example is cracked and how the adhesion performance of the substrate is. When the coating is obviously cracked or the adhesion performance is lower than level 2, the coating quality is unqualified.
[0075] Adhesion performance evaluation: Use a cross-cut knife to make a cross cut on the coating surface, and the cut should be as deep as the substrate. After the cutting is completed, use a soft brush to brush the grid pattern. Use the 600-HC33 test tape produced by 3M Company of the United States, stick the tape on the cross-cut, and then tear it off and repeat twice, and repeat it for the same coating three times. According to the national standard GB-T9286-1998, the coating is tested for cross-cutting. The experimental results range from 5 to 0, among which 0 is the best and 5 is the worst. The first three levels can meet general purposes (0, 1 and 2).
[0076] 3. Sulfur-repellent performance
[0077] 3.1 Determination of sulfur contact angle and sulfur rolling angle
[0078] 3.1.1 Sulfur contact angle measurement
[0079] Heat the coated test sample together with solid sulfur in a beaker at 140 degrees Celsius. After the solid sulfur is liquefied, place the test sample on the contact angle test platform and use a glass needle to extract liquid sulfur. Squeeze out about 2 microliters of liquid sulfur from the glass needle and drop it on the surface of the test sample. Take a contact angle image before the liquid sulfur solidifies. Figure 3 shown.
[0080] 3.1.2 Determination of sulfur rolling angle
[0081] A heating platform is placed and fixed on the surface of the contact angle test platform to heat the test sample. The test sample is heated together with solid sulfur at a temperature of 140 degrees Celsius. After the solid sulfur is liquefied, the test sample is placed on the heating platform for heating. Liquid sulfur is extracted using a glass syringe. About 2 microliters of liquid sulfur is squeezed out of the glass syringe and dropped on the surface of the test sample. The horizontal angle of the contact angle test platform is gradually increased, and photos of the droplet just rolling down are taken. Micro-rolling angle data are as shown in the attached figure. Figure 4 shown.
[0082] 3.1.3θc represents the sulfur contact angle, and α represents the sulfur rolling angle.
[0083] 3.2 The thermal stability, corrosion resistance and mechanical stability of the coating with sulfophobic properties were tested.
[0084] 3.2.1 Thermal stability
[0085] The test samples of the specific embodiments or specific comparative examples coated with the coating are heated in the range of 30°C-180°C for 10h-20h, and the thermal stability of the coating is judged by judging the difference in wettability change of the coating after heating through sulfur contact angle and sulfur rolling angle tests. When the sulfur contact angle and sulfur rolling angle of the coating surface do not change much during the heating process, it indicates that the thermal stability effect is good.
[0086] 3.2.2 Mechanical stability
[0087] A 500-grit sandpaper friction test was performed on the test samples of the specific embodiments or specific comparative examples coated with the coating. One side of the coating was applied to the sandpaper, a 100-gram weight was placed on the coating and pushed back and forth for friction, and the alloy sheet was manually pushed forward 20 cm on the sandpaper. The contact angle and the rolling angle were measured every 10 frictions, and the total number of frictions was 100. During the friction process, there was no significant difference in the sulfur contact angle and the sulfur rolling angle on the coating surface, indicating that the coating had good mechanical stability.
[0088] 3.2.3 Corrosion resistance
[0089] The test samples of the specific embodiments or specific comparative examples coated with the coating are subjected to the corrosive liquid test, and the corrosive liquids (acid, alkali and salt) are respectively prepared by HCl, NaOH and NaCl. The nickel-based alloy sheet with the coating is immersed in the prepared corrosive liquid solution, taken out after soaking for 24 hours, rinsed with deionized water, and dried to test the sulfur contact angle and sulfur rolling angle. When there is no obvious difference in the sulfur contact angle on the coating surface, it means that the coating has good corrosion resistance.
[0090] Example 1-1
[0091] The method for preparing the coating comprises the following steps:
[0092] S1: Disperse 1g of hydrophilic nano-SiO2 with a particle size of 7-40nm in 90g of alcohol and stir evenly, then add 0.5g of ethyl orthosilicate, 8g of ammonia water and 1.5g of 1H,1H,2H,2H-heptadecafluorodecyltrimethoxysilane to the alcohol for reaction, stir at room temperature for 12h, wash the product with anhydrous ethanol several times and centrifuge it. Then put it in an oven at 80℃ and dry it for 4h to obtain the first product;
[0093] S2: Disperse the first product in butyl acetate solution, stir the sol solution at room temperature for 1 hour, then add fluorosilicone resin and curing agent to the sol solution for cross-linking reaction, stir for 2 hours, and prepare a sulfur-repellent and low-sulfur adhesive coating.
[0094] The total weight ratio of the first product, butyl acetate solution, fluorosilicone resin and curing agent is 100wt%, wherein the first product is 8wt%, and the weight ratio of butyl acetate: fluorosilicone resin: curing agent is 10:3:0.3.
[0095] The coating was applied to the surface of a nickel-based alloy sheet (specification: 2*5*0.1 cm long*width*thickness) and cured to obtain a test sample coated with the coating.
[0096] Example 1-2
[0097] The method for preparing the coating comprises the following steps:
[0098] S1: Add 1g of hydrophilic nano ZnO with a particle size of 7-40nm and 1g of 1H,1H,2H,2H-heptadecafluorodecyltrimethoxysilane to 90g of alcohol for reaction, stir at room temperature for 12h, wash the product with anhydrous ethanol several times and centrifuge it. Then put it into an oven at 80℃ and dry it for 4h to obtain the first product;
[0099] S2: The first product in S1 is dispersed in butyl acetate solution, stirred at room temperature for 1 hour to obtain a sol solution, and then fluorosilicone resin and a curing agent are added to the sol solution for cross-linking reaction, stirred for 2 hours, and a sulfur-repellent and low-sulfur adhesive coating is prepared.
[0100] The total weight ratio of the first product, butyl acetate solution, fluorosilicone resin and curing agent is 100wt%, wherein the first product is 8wt%, and the weight ratio of butyl acetate: fluorosilicone resin: curing agent is 10:3:0.3.
[0101] The coating was applied to the surface of a nickel-based alloy sheet (specification: 2*5*0.1 cm long*width*thickness) and cured to obtain a test sample coated with the coating.
[0102] Examples 1-3
[0103] The method for preparing the coating comprises the following steps:
[0104] S1: Add 1g of hydrophilic nano-Al2O3 with a particle size of 30nm and 1g of 1H,1H,2H,2H-heptadecafluorodecyltrimethoxysilane to 90g of alcohol for reaction, stir at room temperature for 12h, wash the product with anhydrous ethanol several times and centrifuge it. Then put it into an oven at 80℃ and dry it for 4h to obtain the first product;
[0105] S2: Disperse the first product in an ethyl acetate solution, stir the sol solution at room temperature for 1 hour, then add epoxy resin and curing agent to the sol solution for cross-linking reaction, stir for 2 hours, and prepare a sulfur-repellent and low-sulfur adhesive coating.
[0106] The total weight ratio of the first product, ethyl acetate solution, epoxy resin and curing agent is 100wt%, wherein the first product is 20wt%, and the weight ratio of ethyl acetate:epoxy resin:curing agent is 10:2:2.
[0107] The coating was applied to the surface of a nickel-based alloy sheet (specification: 2*5*0.1 cm long*width*thickness) and cured to obtain a test sample coated with the coating.
[0108] Example 2
[0109] The preparation method of the coating is as described in Example 1-1, except that the mass percentage of the first product is different. For specific adjustments, refer to the table below.
[0110] Serial number wt% Example 1-1 8 Example 2-1 10 Example 2-2 12 Example 2-3 14 Embodiment 2-4 16
[0111] Blank Group
[0112] Nickel-based alloy sheets (specifications: 2*5*0.1cm long*width*thickness) were used as test samples.
[0113] Comparative Example 1
[0114] Preparation of fluorosilicone coating:
[0115] Fluorosilicone resin and curing agent were added to butyl acetate solution for cross-linking reaction, stirred for 2 hours, and a coating was prepared, which was applied on a nickel-based alloy sheet and cured to obtain a coating. The weight ratio of butyl acetate, fluorosilicone resin and curing agent was 100wt%, and the weight ratio of butyl acetate: fluorosilicone resin: curing agent was 10:3:0.3.
[0116] Comparative Example 2
[0117] The preparation method of the coating is similar to that of Example 1-1, except that the mass percentage of the first product is different. Specifically, the content of the first product is 18 wt %.
[0118] After testing the test samples of the above specific embodiments and specific comparative examples, the obtained performance data are as follows, wherein the sulfur contact angles measured in the specific embodiments in Example 1 and Example 2 are all greater than 90°, having sulfur-repelling properties and the coating quality is qualified, the sulfur contact angle of the fluorosilicone resin coating in Comparative Example 1 is measured to be 74°, which does not achieve sulfur-repelling properties, and Comparative Examples 2 and 3 are severely cracked, which do not meet the requirements for qualified coating quality, therefore, only the specific embodiments in Example 1 and Example 2 are tested for thermal stability, corrosion resistance and mechanical stability:
[0119] Performance data table 1
[0120]
[0121] Performance data table 2-1
[0122]
[0123]
[0124] Performance data table 2-2
[0125]
[0126] Performance data table 2-3
[0127]
[0128] From the above data, we can conclude that:
[0129] By comparing the blank group with Example 1-1, Example 1-2, and Example 1-3, it can be seen that, relative to the test sample to which the coating of the present application is not applied to form a coating, the test sample to which the coating of the present application is applied to form a coating significantly reduces the amount of sulfur deposition within 1 hour, and the coating surface does not crack, and the adhesion performance reaches above 1, with excellent coating quality. It can be seen that the coatings formed by the coatings prepared from different first product sources formed by modifying hydrophilic nano-SiO2, hydrophilic nano-ZnO, and hydrophilic nano-Al2O3 can improve the low-sulfur performance of the test sample, and have good thermal stability, corrosion stability, and mechanical stability. Among them, Example 1-1 is better than Example 1-2 in sulfur-repellent performance. It is speculated that SiO2 is generated under alkaline catalyst conditions and has more -OH groups on the surface, so it is easier to be grafted, thereby allowing the powder to produce better sulfur-repellent performance.
[0130] By comparing Comparative Example 1 with Example 1-1 and Example 1-2, it can be seen that the fluorosilicone resin coating prepared without adding the first product, although the coating quality is acceptable, does not have sulfur-repellent and low-sulfur properties.
[0131] By comparing Comparative Example 2 with Example 1-1, when the mass percentage of the first product is greater than 16wt%, the formed coating is obviously cracked and the coating quality is unqualified. By comparing Example 1-1 and Examples 2-1 to 2-4, it can be seen that the performance of the coating in reducing the amount of sulfur deposition increases with the increase of the mass percentage of the first product, and the adhesion performance of the coating gradually decreases. When the first product is 16wt%, the adhesion performance decreases from level 0 to level 1, which is a relatively obvious decrease. Similar tests in Example 1-1 show that when the mass percentage of the first product is preferably 10-14wt%, the sulfur contact angle can reach 122°-137°, and the sulfur rolling The angle reaches 5.6°~18.9°, the sulfur deposition per hour is less than 2.4mg / cm2, and the coating quality is excellent, the adhesion performance reaches level 0, the sulfur contact angle decreases within 5° and the sulfur rolling angle decreases within 3° in the temperature range of 60°~180°C, the sulfur contact angle decreases within 8° and the sulfur rolling angle decreases within 7° in the pH range of 1~9, and after rubbing with 500 mesh sandpaper, the sulfur contact angle decreases within 3° and the sulfur rolling angle decreases within 0.8°. It can be seen that the mechanical stability of the coating of the present application is the best, the thermal stability is second, and the corrosion stability is the third, but the whole can be maintained at more than 125°, and the excellent sulfur-repelling performance is stably maintained. Wherein, when the mass percentage of the first product is 14wt%, and the weight ratio of butyl acetate: fluorosilicone resin: curing agent is 10:3:0.3, the formed coating has the best comprehensive performance, and embodiment 2-3 is the best embodiment.
[0132] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A method for preparing a coating, characterized in that: The method comprises the following preparation steps: S A1 : Dispersing hydrophilic nano-SiO2 in a solvent, then adding ethyl orthosilicate, ammonia water and 1H,1H,2H,2H-heptadecafluorodecyltrimethoxysilane into the solvent for reaction, and modifying to obtain a first product; or, S A1 : Adding hydrophilic nano ZnO and 1H,1H,2H,2H-heptadecafluorodecyltrimethoxysilane into a solvent for reaction, and modifying to obtain a first product; S A2 :S A1 The first product is dispersed in a butyl acetate solution to obtain a sol solution, and a fluorosilicone resin and a curing agent are added to the sol solution to carry out a cross-linking reaction to prepare a coating; The weight ratio of the first product, the butyl acetate solution, the fluorosilicone resin and the curing agent is 100wt%, the first product is 8-16wt%, and the weight ratio of the butyl acetate: the fluorosilicone resin: the curing agent is 5-15: 1-3: 0.1-0.3; Or use the following steps: S B1 : Add hydrophilic nano-Al2O3 and 1H,1H,2H,2H-heptadecafluorodecyltrimethoxysilane into a solvent for reaction, and modify to obtain a first product; S B2 :S B1 The first product is dispersed in an ethyl acetate solution to obtain a sol solution, and then an epoxy resin and a curing agent are added to the sol solution to carry out a cross-linking reaction to prepare a coating; The weight ratio of the first product, the ethyl acetate solution, the epoxy resin and the curing agent is 100wt% in total, the first product is 16-24wt%, and the weight ratio of the ethyl acetate: the epoxy resin: the curing agent is 5-15:1-3:1-3.
2. The method for preparing a coating according to claim 1, characterized in that: In step S A2 wherein the first product is 10 to 14 wt %; Or, in step S B2 In the method, the first product is 18-22 wt%.
3. The method for preparing the coating according to claim 2, characterized in that: In step S A2 In the embodiment, the first product is 14 wt %; the weight ratio of the butyl acetate: the fluorosilicone resin: the curing agent is 10:3:0.3; Or, in step S B2 In the method, the first product is 20 wt %; the weight ratio of the ethyl acetate: the epoxy resin: the curing agent is 10:2:
2.
4. Application of coating, characterized in that, The coating prepared by the preparation method according to any one of claims 1 to 3 is applied to the inner wall of a wellbore for exploitation of a high-sulfur gas field or the inner wall of a pipeline in a gathering and transportation pipeline system.
5. A method for testing the sulfur contact angle of a coating surface, characterized in that: Applicable to the coating prepared by the preparation method according to any one of claims 1 to 3; The following steps are involved: S D1 , applying the coating to the surface of a substrate and curing it to obtain a test sample of the surface-adherent coating; S D2 , respectively heating the test sample and solid sulfur to 120-160° C., and waiting for the solid sulfur to liquefy; S D3 , Conduct sulfur contact angle test: The test sample is placed on a contact angle test platform, liquid sulfur is drawn and dropped onto the surface of the test sample, and a static contact angle image of the liquid sulfur is taken before the liquid sulfur is cooled and solidified to measure the sulfur contact angle.
6. A method for testing the sulfur rolling angle on a coating surface, characterized in that: Applicable to the coating prepared by the preparation method according to any one of claims 1 to 3; The following steps are involved: S E1 , applying the coating to the surface of a substrate and curing it to obtain a test sample of the surface-adherent coating; S E2 , respectively heating the test sample and solid sulfur to 120-160° C., and waiting for the solid sulfur to liquefy; S E3 , Conduct sulfur rolling angle test: The test sample is placed on a contact angle test platform, and liquid sulfur is dropped onto the surface of the test sample. The temperature of the liquid sulfur is maintained at ≥120°C, and the horizontal angle of the contact angle test platform is gradually increased. Photos of the droplets just rolling down are taken to obtain micro-rolling angle data, and the sulfur rolling angle is measured.
7. A sulfur deposition amount measuring device, characterized in that: Applied to a coating prepared by the preparation method according to any one of claims 1 to 3, the coating is applied to a substrate surface and cured to obtain a test sample (44) of a surface-adherent coating; The invention comprises: a gas mixing system (1), a gas supply system (2), a test container system (4), a sulfur recovery container system (5) and a three-way valve (3), wherein the gas mixing system (1), the gas supply system (2) and the test container system (4) are connected via the three-way valve (3), and the sulfur recovery container system (5) is connected to the test container system (4), wherein: The gas supply system (2) supplies gas to the gas mixing system (1); the gas mixing system (1) heats and sublimates solid sulfur and mixes gaseous sulfur with gas to form a mixed gas, which is then introduced into the test container system (4); the test container system (4) places the test sample (44) and allows the mixed gas to pass through the test sample (44) at a predetermined flow rate, a predetermined pressure and within a predetermined time; the sulfur recovery container system (5) cools and solidifies the mixed gas discharged from the test container system (4) and collects the solid sulfur; The three-way valve (3) comprises a first channel (31), a second channel (32) and a third channel (33); The gas mixing system (1) comprises a gas container (12), the gas container (12) is provided with a heating device (11), and the gas container (12) is connected to the three-way valve (3) through the first channel (31); The gas supply system (2) comprises a gas cylinder (23), the gas cylinder (2) is connected to the second channel (32) via a first pipeline (21), and the first pipeline (21) is connected to a first pressure gauge (22); The test container system (4) comprises a test container (45), the test container (45) is connected to the third channel (33) via a second pipeline (41), the second pipeline (41) comprises a flow valve (42) and a second pressure gauge (43), and the outlet of the test container (4) is connected to the sulfur recovery container system (5) via a third pipeline (51); The sulfur recovery container system (5) comprises a sulfur recovery container (52), the sulfur recovery container (52) is loaded with a cooling liquid (53), and the outlet of the third pipeline (51) is connected to the cooling liquid (53).
8. The sulfur deposition amount measuring device according to claim 7, characterized in that: A metal mesh (46) is arranged at the outlet of the test container (4), and the mesh size of the metal mesh (46) is less than 100 meshes.
9. The sulfur deposition amount measuring device according to claim 7, characterized in that: The sulfur recovery container (5) is a beaker (5), the coolant (53) is water, the heating device (11) is an oven, and the gas loaded in the gas cylinder (2) is carbon dioxide, nitrogen or natural gas.
10. The method for using the sulfur deposition amount measuring device according to any one of claims 7 to 9, characterized in that: The following steps are involved: S C1 , placing solid sulfur in a gas container (1), turning on a heating device (11) so that the temperature in the gas container (1) is 120-160° C., and the solid sulfur melts and sublimates; S C2 , opening the first channel (31) and the second channel (32) of the three-way valve (3) so that the gas supply system (2) can supply gas to the gas mixing system (1), and stopping the ventilation when the pressure displayed by the first pressure gauge (22) is 1 to 3 MPa, and closing the second channel (32) so that the gas container (1) is in a closed state, and the gaseous sulfur is mixed with the gas; S C3 , opening the third channel (33) of the three-way valve (3), preheating for more than 10 minutes, and then passing the mixed gas into the test container (4) through the second pipeline (41) at a predetermined flow rate and a predetermined pressure, placing the relevant test sample (44) in the test container (4), recording the ventilation time, and measuring the sulfur deposition amount on the surface of the test sample (44) at the predetermined time.
Citation Information
Patent Citations
Formula based on modified hydrophobic SiO2 (silicon dioxide) self-cleaning paint and preparation method thereof
CN103254784A
Sulfur deposition device based on magnetic suspension balance
CN104483227A
Preparation method of icing-resistant / corrosion-resistant integrated functional super-hydrophobic coating for aviation
CN109746172A
Core sulfur analysis system
CN111044427A
Sulfur encapsulation of fertilizers to provide controlled dissolution rates
US3576613A